2015
DOI: 10.4330/wjc.v7.i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide: Current status and perspectives in arrhythmia management

Abstract: Flecainide acetate is a class IC antiarrhythmic agent and its clinical efficacy has been confirmed by the results of several clinical trials. Nowadays, flecainide is recommended as one of the first line therapies for pharmacological conversion as well as maintenance of sinus rhythm in patients with atrial fibrillation and/or supraventricular tachycardias. Based on the Cardiac Arrhythmia Suppression Trial study results, flecainide is not recommended in patients with structural heart disease due to high proarrhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 58 publications
0
68
0
9
Order By: Relevance
“… 44 These compounds are sorted in Table 1 according to their IC 50 values. In addition, we included three known drugs – ranolazine, 45 lidocaine, 46 and flecainide 47 – that are known to block hNa v 1.5 in our validation set. All of the ligands were prepared using the LigPrep module in the Schrodinger drug discovery suite, followed by ensemble-based docking against dominant hNa v 1.5 conformations obtained from RMSD clustering.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“… 44 These compounds are sorted in Table 1 according to their IC 50 values. In addition, we included three known drugs – ranolazine, 45 lidocaine, 46 and flecainide 47 – that are known to block hNa v 1.5 in our validation set. All of the ligands were prepared using the LigPrep module in the Schrodinger drug discovery suite, followed by ensemble-based docking against dominant hNa v 1.5 conformations obtained from RMSD clustering.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Flecainide is a trifluoroethoxybenzamide approved for the treatment of AF and/or supraventricular tachycardia. Importantly, flecainide is not recommended to patients with underling structural heart disease as the drug can be pro-arrhythmic in this environment ( Andrikopoulos et al, 2015 ). While flecainide is classed as a type IC antiarrhythmic drug (a Na + channel blocker) it is worth noting here the drugs ability to inhibit RyR2 action by reducing the duration of channel opening ( Figure 4 ).…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
“…The first warning signal for current AADs was the report of the CAST trial results [ 11 , 12 ] demonstrating an increase in mortality with encainide, flecainide and moricizine in patients with structural heart disease. The management of ischemic heart disease changed since then, and flecainide proved to be safer than initially believed [ 13 ]. However, repeated meta-analyses and systematic reviews showed that current AADs have moderate to low efficacy in controlling sinus rhythm at the expense of frequent side effects including severe proarrhythmia and a high withdrawal rate [ 14 ].…”
Section: The Beginning Of the End And The End Of The Beginningmentioning
confidence: 99%